SAVE OR UTILIZE? HISTORY OF CHILD CARE BASED ON RELIGIOUS INSTITUTIONS IN THE COLONIAL ERA - Imam Basthomi (Universitas Negeri Surabaya, 2026)
This article focuses on examining child care practices during the colonial period involving religious organizations. Based on archival sources, the purpose of this study examines the role of religious organizations and institutions in caring for children, particularly those deemed orphaned, impoverished, and neglected. Children in this context became the object of ideological projects of both religious institutions and the colonial government. This study not only highlights child-rearing practices but also reveals the connections between moral values, cultural norms, and colonial power dynamics in the construction of childhood. The method used in this article is historical methods (heuristics, verification, interpretation, and historiography). The findings of this study reveal that religious-based childcare was not only a manifestation of compassion but also part of a broader colonial power project. Childcare was not limited to humanitarian charity, but was a strategy of soft colonialism integrated into the colonial civilizing mission. Orphanages served as instruments of social control, shaping colonial identities and reinforcing hierarchical social structures. These findings are important because they challenge the singular narrative of